“Long COVID-19” and viral “fibromyalgia-ness”: Suggesting a mechanistic role for fascial myofibroblasts (Nineveh, the shadow is in the fascia) - Plaut, Shiloh (Frontiers in Medicine, 2023)
The coronavirus pandemic has led to a wave of chronic disease cases; “Long COVID-19” is recognized as a new medical entity and resembles “fibromyalgia” which, likewise, lacks a clear mechanism. Observational studies indicate that up to 30%–40% of convalescent COVID-19 patients develop chronic widespread pain and fatigue and fulfill the 2016 diagnostic criteria for “fibromyalgia.” A recent study suggested a theoretical neuro-biomechanical model (coined “Fascial Armoring”) to help explain the pathogenesis and cellular pathway of fibromyalgia, pointing toward mechanical abnormalities in connective tissue and fascia, driven by contractile myo/fibroblasts and altered extracellular matrix remodeling with downstream corresponding neurophysiological aberrations. This may help explain several of fibromyalgia’s manifestations such as pain, distribution of pain, trigger points/tender spots, hyperalgesia, chronic fatigue, cardiovascular abnormalities, metabolic abnormalities, autonomic abnormalities, small fiber neuropathy, various psychosomatic symptoms, lack of obvious inflammation, and silent imaging investigations. Pro-inflammatory and pro-fibrotic pathways provide input into this mechanism via stimulation of proto/myofibroblasts. In this hypothesis and theory paper the theoretical model of Fascial Armoring is presented to help explain the pathogenesis and manifestations of “long COVID-19” as a disease of immuno-rheumo-psycho-neurology. The model is also used to make testable experimental predictions on investigations and predict risk and relieving factors.